WEBSITE SECURITY AND HIDING OF SECRET MESSAGES WITH RC4 METHOD AND ADAPTIVE PATTER - Rifqi, Luthfi Ahmad; T.M Diansyah; Lubis, Imran (Bahasa Indonesia, 2025)
The application of technology in the field of data and information security has been carried out a lot. Threats to information security can occur when the information sent is not addressed to everyone but only to certain people, especially if the information provided is confidential. Currently there have been many crimes in cyberspace, where confidential information can be taken by a hacker without being noticed. This raises concerns for the owner of the confidential information. So the purpose of this thesis research is to create a Website for Security and Concealment of Secret Messages with the RC4 Method and Adaptive Pattern which aims to keep secret or hide hidden information so that it is not spread to other unauthorized parties. In the research that has been done, the messages that have been entrusted do not make significant changes to other digital data. It would not physically attract the attention of a potential attacker or hacker, for example an image that looks harmless or not potentially attackable.